Mustard baffle obstruction and leak – How successful are percutaneous interventions in adults?. Issue 2 (December 2015) - Bradley, Elisa A.; Cai, Amanda; Cheatham, Sharon L.; Chisolm, Joanne; Sisk, Tracey; Daniels, Curt J.; Cheatham, John P.
Abstract: Atrial switch operations for D-Transposition of the great arteries (D-TGA) were performed until the late 20th century. These patients have substantial rates of re-operation, particularly for baffle related complications. This study sought to analyze the efficacy of percutaneous transcatheter intervention (PTI) for baffle leak and/or stenosis in adult atrial switch patients. Adult patients with a prior atrial switch operation who underwent heart catheterization (2002–2014) at a tertiary adult congenital heart disease referral center were retrospectively analyzed. In 58 adults (30 ± 8 years, 75% men, 14% New York Heart Association (NYHA) functional class ≥ 2) who underwent 79 catheterizations, PTI was attempted in 50 (baffle leak (n = 10, 20%), stenosis (n = 27, 54%), or both (n = 13, 26%)). PTI was successful in 45 and 5 were referred for surgery due to complex anatomy. A total of 40 bare metal stents, 18 covered stents, 16 occlusion devices, 2 angioplasties, and 1 endovascular graft were deployed. In isolated stenosis, there was improvement in NYHA functional class after PTI (8 vs. 0 patients were NYHA FC > 2, p = 0.004), which was matched by improvement in maximal oxygen consumption on exercise testing (VO2 ) (25.1 ± 5.4 mL/kg/min vs. 27.9 ± 9 mL/kg/min, p = 0.03). There were no procedure-related deaths or emergent surgeries in this cohort. This single-center cohort is the largest reported series of adult atrial switch operation patients who have undergone PTI for baffle stenosis and/or leak. We demonstrate that PTI with an expert multi-disciplinary team is a safe and effective alternative to surgery in adult patients with an atrial switch operation.